eMagRes 1996
DOI: 10.1002/9780470034590.emrstm1338
|View full text |Cite
|
Sign up to set email alerts
|

Environmental NMR: Solid-state Methods

Abstract: Solid-state NMR is widely used to characterize organic matter (OM), including litter inputs, peat, composts, and mineral soil, and to understand the fate of environmental contaminants. The combination of high-power decoupling, magic-angle spinning (MAS), and cross polarization (CP) to enhance sensitivity has greatly facilitated applications to 13 C, with lesser use of 15 N and 31 P. Focusing on 13 C, this article summarizes the development of the field and presents basic concepts of solid-state NMR, pulse sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 123 publications
0
20
0
Order By: Relevance
“…The oldest sample (2,355 ysf) has the highest proportion of aryl C (71%) and aromaticity (0.79). The CP spectra underestimate aromatic C without attached hydrogens; this effect is more important for samples high in O and di-Oalkyl C including carbohydrate but becomes less important as the proportion of aromatic C increases (Baldock and Smernik, 2002;Czimczik et al, 2002;Ascough et al, 2008;McBeath et al, 2011;Preston, 2014;Preston et al, 2014a,b). Our spectra indicate a trend to higher aromaticity with increasing ysf (not shown), but obviously, the low sample size, especially at higher ysf and the qualitative aspect of the NMR areas does not allow us to establish statistical inference.…”
Section: C-13 Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…The oldest sample (2,355 ysf) has the highest proportion of aryl C (71%) and aromaticity (0.79). The CP spectra underestimate aromatic C without attached hydrogens; this effect is more important for samples high in O and di-Oalkyl C including carbohydrate but becomes less important as the proportion of aromatic C increases (Baldock and Smernik, 2002;Czimczik et al, 2002;Ascough et al, 2008;McBeath et al, 2011;Preston, 2014;Preston et al, 2014a,b). Our spectra indicate a trend to higher aromaticity with increasing ysf (not shown), but obviously, the low sample size, especially at higher ysf and the qualitative aspect of the NMR areas does not allow us to establish statistical inference.…”
Section: C-13 Nmrmentioning
confidence: 99%
“…Thus, rather than using a vertical boundary, a baseline for the di-O-alkyl region was sketched in to allow a more accurate estimate of this region. Relative areas were determined by copying the spectra, and cutting and weighing the spectral regions, an old technique that is still useful for spectra with low signal-to-noise ratios (Preston, 2014;Preston et al, 2014a). Aromaticity was calculated as the ratio of intensities 110-165 ppm/0-165 ppm.…”
Section: C-13 Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative abundance of phenolic C was also highest in the mature sludge, which was reflected in a F o r R e v i e w O n l y 14 higher degree aromaticity (aromatic + phenolic C) compared to the other two materials. Peaks at 148ppm for all three materials correspond to C3 in guaiacyl units of condensed and hydrolysable tannins and lignins (Preston 1996). Carbonyl C, the most oxidized form of carbon, was highest for the forest floor material (Table 4).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The small peak at 30 ppm observed for the forest floor corresponds to the methylene groups in long chain aliphatic compounds (Kögel-Knabner 1997;Bartoszek et al 2008) found in waxes and cutins, polyesters of roots and bark, condensed tannins and sidechains of proteins (Preston 1996). The small peaks in the 20 -30 ppm region for the sludges are associated to C-CH 3 moieties (Keeler and Maciel 2000), and the sharper peak at 22 ppm likely corresponds to terminal methyl groups of alkyl chains and to acetyl methyl groups in hemicelluloses (Keeler and Maciel 2000).…”
Section: Nmr Spectroscopymentioning
confidence: 99%